Phase I clinical trial repurposing all-trans retinoic acid as a stromal targeting agent for pancreatic cancer - Hemant M. Kocher (Nature Portfolio, 2020)
All-trans retinoic acid - ATRA- is known to remodulate the stroma of pancreatic cancer in mice. Here, the authors carried out a Phase Ib trial in pancreatic patients and show that ATRA in combination with chemotherapy is a safe potential treatment for patients with advanced pancreatic cancer, and demonstrate a stromal modulatory effect.